Energy potential of wood waste from a tropical urban forest (Research, Society and Development, 2020)
Urban tropical forest species generate large amounts of wood waste by pruning and removing urban trees, which can be an accessible source of biomass that could be used to generate energy instead of being disposed of irregularly. The objective of this study was to evaluate the potential for energy production of the wood residue of seven species most used in urban forestry in the State of São Paulo, Brazil, by determining the physical, chemical and energetic characteristics. Wood waste of 7 common urban forests species in the State of São Paulo were collected in the city of Piracicaba, characterized (humidity, basic density and bulk density), chemically (extract content, volatile materials, fixed carbon and ash content) and energetically (higher, lower, useful calorific power, density energy and thermogravimetric analysis). The highest value of basic density was found in the species Cenostigma pluviosum (653.76 kg/m³), ​​all species had higher calorific values ​​greater than 19 MJ/kg and the energy density of the species varied between 4.45 to 10,80 GJ/m³. The use of these wood residues for direct combustion is a viable alternative and can be considered as a solution to replace the incorrect disposal, which is still a common practice in many cities in developing countries.